Tomato Seed Coat Permeability to Selected Carbon Nanomaterials and Enhancement of Germination and Seedling Growth - Tatsiana A. Ratnikova; Ramakrishna Podila; Apparao M. Rao; Alan G. Taylor (The Scientific World Journal)
Seed coat permeability was examined using a model that tested the effects of soaking tomato (Solanum lycopersicon) seeds in combination with carbon-based nanomaterials (CBNMs) and ultrasonic irradiation (US). Penetration of seed coats to the embryo by CBNMs, as well as CBNMs effects on seed germination and seedling growth, was examined. Two CBNMs, C60(OH)20 (fullerol) and multiwalled nanotubes (MWNTs), were applied at 50 mg/L, and treatment exposure ranged from 0 to 60 minutes. Bright field, fluorescence, and electron microscopy and micro-Raman spectroscopy provided corroborating evidence that neither CBNM was able to penetrate the seed coat. The restriction of nanomaterial (NM) uptake was attributed to the semipermeable layer located at the innermost layer of the seed coat adjacent to the endosperm. Seed treatments using US at 30 or 60 minutes in the presence of MWNTs physically disrupted the seed coat; however, the integrity of the semipermeable layer was not impaired. The germination percentage and seedling length and weight were enhanced in the presence of MWNTs but were not altered by C60(OH)20. The combined exposure of seeds to NMs and US provided insight into the nanoparticle-seed interaction and may serve as a delivery system for enhancing seed germination and early seedling growth.